2021
DOI: 10.3389/fdata.2021.654914
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for a Dashboard to Support Quality Improvement Teams in Pain Management

Abstract: Pain management is often considered lower priority than many other aspects of health management in hospitals. However, there is potential for Quality Improvement (QI) teams to improve pain management by visualising and exploring pain data sets. Although dashboards are already used by QI teams in hospitals, there is limited evidence of teams accessing visualisations to support their decision making. This study aims to identify the needs of the QI team in a UK Critical Care Unit (CCU) and develop dashboards that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While some of these have been shown to improve quality and safety outcomes [13,14], overall the benefit of quality and safety dashboards is contested, with recent paradigms attributing the absence of improvements to a lack of inclusion of health professionals' perspectives [10][11][12]. Studies have shown that without the inclusion of health professionals during development, these dashboards can lack usefulness (eg, display content that is perceived as irrelevant and unreliable by the user) and usability (eg, visualize data in an incomprehensible way) [10,11,20]. Moreover, enforcing the use of dashboards in a "top-down" manner can interfere with professionals' autonomy and routines, making dashboards a burden to users [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…While some of these have been shown to improve quality and safety outcomes [13,14], overall the benefit of quality and safety dashboards is contested, with recent paradigms attributing the absence of improvements to a lack of inclusion of health professionals' perspectives [10][11][12]. Studies have shown that without the inclusion of health professionals during development, these dashboards can lack usefulness (eg, display content that is perceived as irrelevant and unreliable by the user) and usability (eg, visualize data in an incomprehensible way) [10,11,20]. Moreover, enforcing the use of dashboards in a "top-down" manner can interfere with professionals' autonomy and routines, making dashboards a burden to users [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…New digital tools are emerging rapidly, with health and environmental institutions increasingly collecting larger amounts of data and facing novel opportunities to adopt technologies to manage such data for improved decision-making (1)(2)(3). Nevertheless, the way data is being gathered, analyzed and reported to policymakers has been far from enabling structured analyses and from identifying relevant policy issues in the environmental health (EH) domain (4).…”
Section: Introductionmentioning
confidence: 99%